Senior High School Students' Perceptions on the Effectiveness of Online English Learning during Covid-19 Pandemic: A Survey Research - Anggyta, Heyba Fatwa; Rofiq, Annur; Puspa, Areta (English Education Study Program, 2024)
Nowadays, the Internet is undoubtedly indispensable and has become a part in almost everyone’s life and there are 175.4 million internet users in Indonesia based on data from survey conducted by an organization which called We Are Social in 2020 (Krishnapatria, 2020). Therefore, one of the utilizations of the internet is the development of online learning and one of massive implementation of online learning occurred during pandemic. Thus, This research was aimed to reveal students’ perception towards English online learning in their school during pandemic time. This research applied survey research design and the data that have been collected then analyzed by applying Descriptive Statistics in the form of percentage and nonparametric Wilcoxon signed rank. It found out that students’ perception towards English online learning tend to be not better compared with face-to-face learning.